Quantification of phospholipids and glycerides in human milk using ultra-performance liquid chromatography with quadrupole-time-of-flight mass spectrometry - Liu, Yan; Qiao, Weicang; Liu, Yanpin; Zhao, Junying; Liu, Qian; Yang, Kai; Zhang, Minghui; Wang, Yaling; Liu, Yan; Chen, Lijun (Frontiers in Chemistry, 2023)
Human milk lipids, which are an important source of energy and affect growth and development of infants, require a comprehensive method for its qualitative and quantitative analysis. This work describes a high-throughput method for the analysis of phospholipids, glycerides, free fatty acids and gangliosides in human milk by ultra-performance liquid chromatography (UPLC) using a C18 column with quadrupole-time-of-flight mass spectrometry (Q-TOF-MS). The lipids were extracted by liquid-liquid extraction (LLE) and phospholipids were separated by solid phase extraction (SPE). The chromatographic columns with two different specifications (4.6 mm × 150 mm, and 3 mm × 50 mm) were used to detect phospholipids and glycerides in human milk, respectively. The sphingolipids and glycerides were analyzed in positive ion mode, and the glycerophospholipids and free fatty acids were analyzed in negative ion mode. Both internal and external standards were used for absolute quantification in this experiment. 483 species of lipids, including phospholipids, glycerides, free fatty acids and gangliosides, in human milk were analyzed using UPLC-Q-TOF-MS with high sensitivity and good linearity, with coefficient of correlation above 0.99, the relative standard deviation of accuracy and precision less than 10%. The results in a large number of human milk samples showed that this method was suitable for qualitative and quantitative analysis of lipids in human milk, even for other mammalian milk and infant formulae.